BATF-JUN is critical for IRF4-mediated transcription in T cells - Li, Peng (2012)
Interferon regulatory factor 4 (IRF4) is an IRF family transcription factor with critical roles in lymphoid development and in regulating the immune response(1,2). IRF4 binds DNA weakly due to a C-terminal auto-inhibitory domain, but cooperative binding with factors such as PU.1 or SPIB in B cells increases binding affinity(3), allowing IRF4 to regulate genes containing ETS/IRF composite elements (EICEs; 5′-GGAAnnGAAA-3′)(1). Here, we show that in CD4(+) T cells, where PU.1/SPIB expression is low, and in B cells, where PU.1 is well expressed, IRF4 unexpectedly can cooperate with Activator Protein-1 (AP-1) complexes to bind to AP-1/IRF4 composite (TGAnTCA/GAAA) motifs that we denote as AP-1/IRF composite elements (AICEs). Moreover, BATF/Jun family protein complexes cooperate with IRF4 in binding to AICEs in pre-activated CD4(+) T cells stimulated with IL-21 and in Th17 differentiated cells. Importantly, BATF binding was diminished in Irf4(−/−) T cells and IRF4 binding was diminished in Batf(−/−) T cells, consistent with functional cooperation between these factors. Moreover, we show that AP-1 and IRF complexes cooperatively promote transcription of the Il10 gene, which is expressed in Th17 cells and potently regulated by IL-21. These findings reveal that IRF4 can signal via complexes containing ETS or AP-1 motifs depending on the cellular context, thus indicating new approaches for modulating IRF4-dependent transcription.